PRESENT 2020: Text expanding on the checklist for proper reporting of evidence in sport and exercise nutrition trials - Betts, J. A.; Gonzalez, J. T.; Burke, L. M.; Close, G. L.; Garthe, I.; James, L. J.; Jeukendrup, A. E.; Morton, J. P.; Nieman, D. C.; Peeling, P.; Phillips, S. M.; Stellingwerff, T.; et al. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
The CONSORT (CONsolidated Standards Of Reporting Trials) 2010 guidelines (http://www.consort-statement.org/consort-2010) were developed to improve the reporting of parallel-group randomized controlled trials, whereby compliance with established standards can be demonstrated via completion of the CONSORT 2010 checklist (Schulz et al., 2010). Leading medical journals have endorsed this initiative, which has undoubtedly improved the conduct and reporting of clinical and health care research. Research in the field of sports nutrition and exercise metabolism stands to benefit from similar standards, but it commonly involves research designs other than parallel-group trials, such as cross-over experiments.